1999
DOI: 10.1021/la990796j
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly and Antioxidant Properties of Octanoyl-6-O-ascorbic Acid

Abstract: Vitamin C acts as a powerful radical scavenger, and can be used as a convenient antioxidant agent in aqueous media. To extend its properties to nonaqueous environments, alkanoyl-6-O-ascorbic acid esters with different chain lengths were synthesized, and their micellar and antioxidant properties were investigated by surface tension, viscosity, light scattering, neutron scattering, oxygen uptake, and UV/VIS spectra. According to our results, octanoyl-ascorbic acid forms nearly spherical micelles in water solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 34 publications
5
70
0
1
Order By: Relevance
“…Lo Nostro et al first demonstrated the ability of ampiphilic ascorbic acid esters to self aggregate and form micellar structures in an aqueous media [17]. The nanocarriers retained the antioxidant activity due to the presence of ascorbyl moiety in the polar head group, while the inner micellar provides a hydrophobic core.…”
Section: Introductionmentioning
confidence: 99%
“…Lo Nostro et al first demonstrated the ability of ampiphilic ascorbic acid esters to self aggregate and form micellar structures in an aqueous media [17]. The nanocarriers retained the antioxidant activity due to the presence of ascorbyl moiety in the polar head group, while the inner micellar provides a hydrophobic core.…”
Section: Introductionmentioning
confidence: 99%
“…The reducing activity of vitamin C, its ester derivatives and various commercially available natural antioxidants were determined and compared (Figure 3) [5]. This study shows that ascorbyl esters are high potential antioxidants with radical scavenging capability.…”
Section: Antioxidant and Pharmaceutical Uses Of Ascorbyl Estersmentioning
confidence: 99%
“…15) From the assumption that the micellar solution of the molar ratio of 5 was composed of the 1 : 2 complex of N-4472 and VC with the molecular weight of 930, the association number of the 1 : 2 complex was anticipated to be 15 from the weight-average molecular weight (14000), being consistent with the result reported by Schreier et al Nostro et al investigated the surface active properties of VC derivatives (ASC 8, ASC 10, ASC 12) which were C 8, C 10 and C 12 esters of VC, they reported that all VC derivatives had surface active properties which were due to their amphiphilic structure comprising both hydrophilic VC moiety and hydrophobic alkyl chain. 16) They also reported that ASC 8 with the shortest alkyl chain was freely soluble in water through micelle formation, whereas ASC 10 and ASC 12, the hydrophobic moiety consisting of longer alkyl chains, showed low aqueous solubility and no micelle formation. 16) These results could be attributable to the difference in the hydrophilic-hydrophobic balance (HLB) values of the amphiphilic VC derivatives.…”
Section: )mentioning
confidence: 99%
“…16) They also reported that ASC 8 with the shortest alkyl chain was freely soluble in water through micelle formation, whereas ASC 10 and ASC 12, the hydrophobic moiety consisting of longer alkyl chains, showed low aqueous solubility and no micelle formation. 16) These results could be attributable to the difference in the hydrophilic-hydrophobic balance (HLB) values of the amphiphilic VC derivatives. As shown in Fig.…”
Section: )mentioning
confidence: 99%